Conformational Preferences of Allene Ketones in Lewis Base Catalysis: Synthesis of 4H‐Pyrans and 3, 4‐Dihydro‐2H‐pyrans via α‐Regioselective [4+2] Annulations of γ‐Substituted Allene Ketones and Activated Alkenes. Issue 12 (10th November 2021) - Hou, Rongrong; Wang, Ziyu; Peng, Jia; Yuan, Ye; Zhang, Jingli; Wang, Du; Sun, Taolei
Abstract: A Lewis base‐catalyzed exclusively α ‐regioselective [4+2] annulation of γ ‐substituted allene ketones with 2‐arylidene‐1, 3‐indanediones to construct highly functionalized 3, 4‐dihydro‐2 H ‐pyran isomers have been developed. The annulation reaction initiates with addition of NR3 /PR3 to s ‐ cis ‐ or s ‐ trans ‐allene ketone to generate two geometrically distinct zwitterionic isomers, and the ratio of the two zwitterionic isomers depends on catalyst‐controlled conformation preference of s‐cis / s‐trans‐ allene ketone. By utilizing cinchonine as the catalyst, s‐trans ‐allene ketone usually leads to preferential formation of (3 S, 4 S )‐3‐benzoyl‐4‐ phenyl‐3, 4‐dihydro‐2 H ‐pyran isomer 3 . In contrast, s‐cis‐ allene ketone mainly favors the formation of (3 R, 4 S )‐3‐benzoyl‐4‐phenyl‐3, 4‐dihydro‐2 H ‐pyran isomer 5 under the catalysis of R, S ‐Josiphos‐1 . It's worth noting that only (3 S, 4 S )‐3‐benzoyl‐4‐phenyl‐ 3, 4‐dihydro‐2 H ‐pyran half‐chair isomer 3 can easily isomerize into 4 H ‐pyran. Density functional theory calculations elucidated the origin of considerable difference in isomerization between isomer 3 and isomer 5 . Abstract : Conformational preferences of s–cis / s–trans allenes in phosphine/amine‐catalyzed [4+2] annulation reaction between allene ketones and activated alkenes have been developed. This reaction leads to an exclusive α ‐regioselectivity, highly geometric selectivity, and a conformation selectivity in the construction of isomers 3 and 5 . DFT calculations elucidated the origin of considerable difference in isomerization between these two isomers.